2021
DOI: 10.1128/mbio.03305-20
|View full text |Cite
|
Sign up to set email alerts
|

ROP16-Mediated Activation of STAT6 Suppresses Host Cell Reactive Oxygen Species Production, Facilitating Type III Toxoplasma gondii Growth and Survival

Abstract: Polymorphic effector proteins determine the susceptibility of Toxoplasma gondii strains to IFN-γ-mediated clearance mechanisms deployed by murine host cells. However, less is known about the influence of these polymorphic effector proteins on IFN-γ-independent clearance mechanisms. Here, we show that deletion of one such polymorphic effector protein, ROP16, from a type III background leads to a defect in parasite growth and survival in unstimulated human fibroblasts and murine macrophages. Rescue of these defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 71 publications
0
29
0
Order By: Relevance
“…Having determined that ROP16 III -dependent host cell manipulation is essential for efficient type III encystment, we next sought to determine what domains or functions of ROP16 were required for this phenotype. To accomplish this goal, we used a previously generated panel of IIIΔ rop16 complemented strains 37 . This panel of strains includes ROP16 mutants which are catalytically inactive (ROP16 IIIKD ) or lack a nuclear localization sequence (ROP16 IIIΔNLS ) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Having determined that ROP16 III -dependent host cell manipulation is essential for efficient type III encystment, we next sought to determine what domains or functions of ROP16 were required for this phenotype. To accomplish this goal, we used a previously generated panel of IIIΔ rop16 complemented strains 37 . This panel of strains includes ROP16 mutants which are catalytically inactive (ROP16 IIIKD ) or lack a nuclear localization sequence (ROP16 IIIΔNLS ) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This panel of strains includes ROP16 mutants which are catalytically inactive (ROP16 IIIKD ) or lack a nuclear localization sequence (ROP16 IIIΔNLS ) ( Fig. 3A ) 37 . In addition, as prior work demonstrated that a single polymorphic amino acid on ROP16 determined the strain-specific activation of STAT3/5a/6 34 , this panel also included strains which express a ROP16 III in which the leucine at position 503 was switched to a serine, rendering it “STAT-dead” (ROP16 IIISD ), and a strain that expresses a ROP16 II in which the serine at position 503 was changed to a leucine, rendering it “STAT-active” (ROP16 IISA ) 37 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, direct phosphorylation of STAT3 by ROP16 mimics the IL-10 activity and downregulates IFN-γ, hence enhancing the virulence of T. gondii [134]. Recently, ROP16-mediated activation of STAT6 proved important for type III T. gondii survival through suppression of host cell reactive oxygen species production [136]. Moreover, ROP16 kinase activity silences the cyclin B1 gene promoter, hijacking the function of the host cell epigenetic machinery [137].…”
Section: Rhoptry Organellesmentioning
confidence: 99%